Solid-state electrolyte membrane, method for preparing the same, and battery
Patent Information
- Application Number
- CN202611039551.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-13
- Publication Date
- 2026-10-09
AI Technical Summary
在众多固态电解质体系中,以锂镧锆氧(LLZO)为代表的氧化物陶瓷电解质和以聚环氧乙烷(PEO)基体系为代表的聚合物电解质,是目前研究最多的两类固态电解质,然而,在实际产业化应用中,前述两类电解质存在以下问题:(1)高成本:传统锂镧锆氧(LLZO)需高温烧结,能耗高且原料昂贵;(2)机械强度不足:聚合物电解质(如PEO)室温脆性大,易开裂;(3)界面阻抗高:电极/电解质界面锂枝晶生长导致短路风险;(4)环保性差:溶剂多含有机毒性物质,工艺复杂
(1)通过多孔无机骨架与填充其孔隙的凝胶电解质协同,能够形成固态电解质膜整个的多孔3D骨架,进而构建连续的离子传输通道,加速离子扩散,局部富集Li+,离子电导率可提升50%以上,同时凝胶网络填充多孔无机骨架孔隙,能够消除界面接触电阻,界面阻抗骤降。
Smart Images

Figure CN122889822A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery technology, and more specifically, to a solid electrolyte membrane, its preparation method, and a battery. Background Technology
[0002] Solid-state lithium batteries use solid electrolytes instead of traditional liquid electrolytes, which is expected to fundamentally solve the safety problem of batteries and may achieve higher energy density. Among the many solid electrolyte systems, oxide ceramic electrolytes represented by lithium lanthanum zirconium oxide (LLZO) and polymer electrolytes represented by polyethylene oxide (PEO) are the two most studied solid electrolytes. However, in actual industrial applications, the above two types of electrolytes have the following problems: (1) High cost: Traditional lithium lanthanum zirconium oxide (LLZO) requires high-temperature sintering, which consumes a lot of energy and the raw materials are expensive; (2) Insufficient mechanical strength: Polymer electrolytes (such as PEO) are brittle at room temperature and are prone to cracking; (3) High interfacial impedance: Lithium dendrite growth at the electrode / electrolyte interface leads to short circuit risk; (4) Poor environmental performance: The solvents often contain organic toxic substances and the process is complicated.
[0003] Therefore, existing technologies need to be improved. Summary of the Invention
[0004] In view of this, the purpose of this invention is to at least partially solve one of the technical problems in the related art. To this end, this invention provides a solid electrolyte membrane, its preparation method, and a battery. By constructing a solid electrolyte base membrane with a porous interpenetrating network, and in conjunction with a buffer layer on the surface of the base membrane, the ionic conductivity and mechanical strength can be greatly increased. The assembled battery exhibits high safety and ultra-fast charging capability.
[0005] To solve the above-mentioned technical problems, the present invention is implemented as follows: According to one aspect of the present invention, a solid electrolyte membrane is provided, comprising a base membrane and a buffer layer disposed on at least one surface of the base membrane along its thickness direction; the porosity of the solid electrolyte membrane is not less than 20%; the base membrane comprises an inorganic framework, a gel electrolyte, and a binder; the inorganic framework comprises a porous silica-oxygenated inorganic framework material and a metal oxide; the gel electrolyte comprises a flexible crosslinked polymer and a lithium salt.
[0006] In some of these embodiments, the base film has a three-dimensional interpenetrating network structure.
[0007] In some of these embodiments, the buffer layer comprises at least one of Li3N, LLZO, and Al2O3.
[0008] In some embodiments, the binder is distributed between the inorganic framework and the gel electrolyte.
[0009] In some of these embodiments, the adhesive includes at least one of CMC adhesive, PAA adhesive, PVA adhesive, and PEO adhesive.
[0010] In some embodiments, the porous silica-oxygenated inorganic framework material and the metal oxide are bonded together by intermolecular forces to form an inorganic framework network.
[0011] In some embodiments, the porous silica-oxygenated inorganic framework material includes at least one of diatomaceous earth, zeolite, mesoporous silica, and montmorillonite.
[0012] In some of these embodiments, the metal oxide includes at least one of ZnO, TiO2, and Al2O3.
[0013] In some embodiments, the flexible crosslinked polymer has a gel network structure consisting of a natural polymer backbone and a crosslinked phase.
[0014] In some embodiments, the lithium salt is adsorbed onto the flexible cross-linked polymer to form an ion transport network.
[0015] In some of these embodiments, the lithium salt comprises LiTFSI and / or LiPF6.
[0016] In some embodiments, the mass ratio of the natural polymer backbone to the crosslinked phase is (0.5~7.5):1.
[0017] In some embodiments, the natural polymeric framework is formed from a natural polymeric material, including at least one of cellulose nanofibers, chitosan, and sodium alginate.
[0018] In some embodiments, the crosslinked phase is formed of a polymeric material having hydroxyl and / or carboxyl groups, including at least one of polyvinyl alcohol, gelatin, carboxymethyl chitosan, and natural rubber.
[0019] In some embodiments, the base film further includes a conductive material loaded on the porous silica-oxygenated inorganic framework material to form a charge transport network.
[0020] In some embodiments, the base film further includes a conductive material having C=O groups, wherein the C=O groups in the conductive material are bonded to the Si-O-Si in the porous silica-oxygenated inorganic framework material via hydrogen bonds.
[0021] In some embodiments, the base film further includes a conductive material, which includes a carbon-based conductive material; the carbon-based conductive material includes at least one of graphene quantum dots, multi-walled carbon nanotubes, and graphene oxide.
[0022] In some embodiments, the base film further includes a conductive material, wherein the mass ratio of the conductive material to the porous silica-oxygenated inorganic framework material is 1:(8~10).
[0023] In some embodiments, the porosity of the solid electrolyte membrane is 22% to 40%.
[0024] In some embodiments, the specific surface area of the solid electrolyte membrane is 100 m². 2 / g~220m 2 / g.
[0025] In some embodiments, the inorganic framework has a mass content of 29% to 85% in the base film.
[0026] In some embodiments, the gel electrolyte has a mass content of 5% to 67% in the base membrane.
[0027] In some embodiments, the adhesive content in the base film is 1% to 15% by mass.
[0028] In some embodiments, the mass ratio of the porous silica-oxygenated inorganic framework material to the metal oxide is (1.25~15):1.
[0029] In some embodiments, the mass ratio of the lithium salt to the flexible crosslinked polymer is (0.5~6):1.
[0030] In some embodiments, the thickness of the base film is 0.5 mm to 1 mm.
[0031] In some of these embodiments, the thickness of the buffer layer is 20 nm to 40 nm.
[0032] According to another aspect of the present invention, a method for preparing a solid electrolyte membrane is provided, comprising the following steps: a) A slurry containing a porous silica-oxygenated inorganic framework material is first mixed with a solution containing a gel precursor, a lithium salt, and a crosslinking agent to obtain a mixed slurry; then the mixed slurry is spray-dried to obtain an intermediate. b) The intermediate obtained in step a) and the metal oxide are ball-milled to obtain a ball milling material; then, in the presence of water, the binder is mixed with the ball milling material for the second time, and then the mixture is successively molded and dried to obtain a base film; c) Deposit a buffer material onto the base film obtained in step b) to form a buffer layer, thereby obtaining a solid electrolyte membrane.
[0033] In some of these embodiments, in step a), the conditions for the first mixing include stirring at room temperature for 18 to 30 hours.
[0034] In some of these embodiments, in step a), the spray drying conditions include: an inlet air temperature of 80°C to 100°C, an outlet temperature of 60°C to 70°C, an atomization pressure of 0.2MPa to 0.3MPa, and a feed rate of 30mL / min to 40mL / min.
[0035] In some of these embodiments, in step b), the ball milling is a wet ball milling process, and the conditions for the wet ball milling include: a rotation speed of 200 rpm to 500 rpm and a time of 1 h to 3 h.
[0036] In some of these embodiments, in step b), the conditions for the second mixing include stirring at room temperature for 0.5 h to 2 h.
[0037] In some of these embodiments, in step b), the molding is cold pressing, and the conditions for cold pressing include: a temperature of 20°C to 30°C, a pressure of 10MPa to 20MPa, and a time of 1min to 10min.
[0038] In some embodiments, in step c), the deposition is performed by chemical vapor deposition (CVD) under the following conditions: substrate temperature of 100°C to 300°C and sputtering power of 0.1 kW / cm². 2 ~1kW / cm 2 The working gas is an inert gas, the deposition working gas pressure is 0.2 Pa to 1.5 Pa, and the deposition time is 10 min to 30 min.
[0039] In some embodiments, the porosity of the porous silica-oxygenated inorganic framework material is >90%.
[0040] In some embodiments, the porous silica-oxygenated inorganic framework material has a pore size (PDI) of 0.6 to 0.75.
[0041] In some embodiments, the surface roughness Ra of the porous silica-oxygenated inorganic framework material is 50 nm to 200 nm.
[0042] In some embodiments, the porous silica-oxygenated inorganic framework material includes at least one of diatomaceous earth, zeolite, mesoporous silica, and montmorillonite.
[0043] In some embodiments, the porous silica-oxygenated inorganic framework material includes a porous silica-oxygenated inorganic framework material that has undergone acid treatment, washing, drying, and calcination; the acid treatment conditions include microwave acid washing in the presence of dilute hydrochloric acid; the calcination conditions include calcination under an inert atmosphere at a temperature of 600°C to 800°C for 1 to 3 hours.
[0044] In some embodiments, the gel precursor comprises a natural polymer material, which includes at least one of cellulose nanofibers, chitosan, and sodium alginate.
[0045] In some embodiments, the crosslinking agent comprises a polymeric material having hydroxyl and / or carboxyl groups.
[0046] In some of these embodiments, the crosslinking agent has an average molecular weight of 85,000 g / mol to 130,000 g / mol.
[0047] In some of these implementations, the intermediate Dv 50 The particle size is 5μm~10μm.
[0048] In some embodiments, the particle size of the metal oxide is 10 nm to 50 nm.
[0049] In some of these embodiments, the buffer material includes at least one of Li3N, LLZO, and Al2O3.
[0050] In some embodiments, the slurry comprising the porous silica-oxygenated inorganic framework material further includes a conductive material, and / or a conductive material is added during the ball milling process; the mass ratio of the conductive material to the porous silica-oxygenated inorganic framework material is 1:(8~10).
[0051] In some embodiments, the solid content of the mixed slurry is 10% to 30%.
[0052] In some embodiments, the mass ratio of the porous silica-oxygenated inorganic framework material to the gel precursor is (5~45):(1.5~7.5).
[0053] In some embodiments, the mass ratio of the gel precursor to the lithium salt is (0.5~7.5):(5~15).
[0054] In some embodiments, the mass ratio of the gel precursor to the crosslinking agent is (1.5~7.5):(1~3).
[0055] In some embodiments, the mass ratio of the porous silica-oxygenated inorganic framework material to the metal oxide is (2~20):(1~8).
[0056] In some embodiments, the mass ratio of the porous silica-oxygenated inorganic framework material to the binder is (10~60):(1~3).
[0057] According to another aspect of the present invention, the present invention provides a battery comprising a positive electrode, a negative electrode, and a solid electrolyte membrane disposed between the positive electrode and the negative electrode, wherein the solid electrolyte membrane comprises the solid electrolyte membrane of any of the above embodiments or a solid electrolyte membrane prepared by the preparation method of the solid electrolyte membrane of any of the above embodiments.
[0058] Implementing the technical solution of the present invention has at least the following beneficial effects: (1) Through the synergy of a porous inorganic framework and a gel electrolyte filling its pores, a porous 3D framework of the entire solid electrolyte membrane can be formed, thereby constructing continuous ion transport channels, accelerating ion diffusion, and locally enriching Li. + The ionic conductivity can be increased by more than 50%, and the gel network fills the pores of the porous inorganic framework, which can eliminate interfacial contact resistance and cause a sharp drop in interfacial impedance.
[0059] (2) The metal oxides in the inorganic framework and the lithium salts in the gel electrolyte can work together to optimize the ion transport environment, which helps to reduce polarization at the electrode / electrolyte interface and improve the rate performance of the battery.
[0060] (3) Through the synergistic effect of the binder and the flexible cross-linked polymer, the inorganic skeleton and the gel electrolyte are tightly integrated to form a stable composite structure, thereby enhancing the mechanical strength of the base film, which helps to suppress dendrite puncture and improve the dimensional stability at high temperature.
[0061] (4) A buffer layer set on at least one side of the base film can effectively isolate the direct contact between the electrode and the electrolyte, reduce interfacial side reactions, and improve the cycle performance of the battery.
[0062] (5) The synergistic effect of the buffer layer, the metal oxides in the inorganic framework and the lithium salt in the gel electrolyte can improve the safety of the battery in terms of physical barrier, thermal stability and electrochemical stability.
[0063] Additional aspects and advantages of the invention will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of the invention. Attached Figure Description
[0064] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.
[0065] Figure 1 This is a SEM scan of the diatomaceous earth in Example 1.
[0066] Figure 2 This is a SEM scan of the solid electrolyte membrane in Example 1.
[0067] Figure 3 The image shows the Fourier transform infrared (FTIR) spectrum of the solid electrolyte membrane in Example 1.
[0068] The accompanying drawings have illustrated specific embodiments of the invention, which will be described in more detail below. These drawings and descriptions are not intended to limit the scope of the invention in any way, but rather to illustrate the concept of the invention to those skilled in the art through reference to particular embodiments. Detailed Implementation
[0069] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention.
[0070] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges or individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0071] In the description of this invention, "same chemical composition" should be interpreted broadly, that is, the main components of the two have the same chemical composition, or the two have substantially the same chemical composition, but may have errors or impurities within the acceptable range that can be understood by those skilled in the art.
[0072] In the description of this invention, "A and / or B" can include any of the cases of A alone, B alone, or A and B, where A and B are merely examples and can be any technical feature connected by "and / or" in this invention.
[0073] Unless otherwise specified, the terms "comprising" and "including" as used in this invention can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.
[0074] Unless otherwise specified, all embodiments and optional embodiments of the present invention can be combined with each other to form new technical solutions.
[0075] Unless otherwise specified, all technical features and optional technical features of this invention can be combined to form new technical solutions.
[0076] Unless otherwise specified, all steps of the present invention may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order; for example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0077] Unless otherwise specified, room temperature in this invention refers to 20°C to 30°C.
[0078] In the field of solid-state electrolytes, to achieve a balance between high ionic conductivity, good mechanical strength, and excellent interfacial stability, the commonly used solid-state electrolyte systems are mainly divided into two categories: oxide ceramic electrolyte systems and polymer electrolyte systems. As mentioned above, these two systems suffer from problems such as high cost, insufficient mechanical strength, high interfacial impedance, and poor environmental friendliness.
[0079] After in-depth research, this invention proposes a solid electrolyte based on porous silica-oxygen inorganic framework material, which can improve ionic conductivity and lithium-ion transference number, and has good mechanical strength and interface stability.
[0080] In view of this, some embodiments of the present invention provide a solid electrolyte membrane, including a base membrane and a buffer layer disposed on at least one surface of the base membrane along the thickness direction; the porosity of the solid electrolyte membrane is not less than 20%; the base membrane includes an inorganic framework, a gel electrolyte and a binder; the inorganic framework includes porous silica-oxygenated inorganic framework materials and metal oxides; the gel electrolyte includes a flexible crosslinked polymer and a lithium salt.
[0081] In this invention, the inorganic framework of the base membrane provides rigid mechanical support and abundant hierarchical channels for the entire membrane. The gel electrolyte fills and permeates the pores of the inorganic framework, providing a continuous, low-resistance lithium-ion transport medium. The binder acts as a bridge and fixator, tightly integrating the inorganic framework and the gel electrolyte together to prevent delamination during cycling. The combination of the inorganic framework, gel electrolyte, and binder enables the base membrane to form a stable, ion-channel-free composite at the microscopic level. By setting a buffer layer on the surface of the base membrane, direct contact between the electrode (especially the negative electrode) and the electrolyte can be effectively isolated, thereby blocking electron penetration, avoiding internal micro-short circuits, and ultimately achieving high ionic conductivity, good mechanical strength, and excellent interfacial stability.
[0082] In some embodiments, the base membrane has a three-dimensional interpenetrating network structure. The polymer network of the gel electrolyte can penetrate and fill the hierarchical pores of the inorganic framework, and even partially bond with the surface of the inorganic framework through forces such as hydrogen bonds, thereby forming a three-dimensional interpenetrating network structure in which the inorganic framework network and the gel network interpenetrate and interlock at the microscopic level. This can significantly reduce the tortuosity of the ion transport path and the diffusion barrier in the solid electrolyte membrane, and effectively improve the ionic conductivity.
[0083] The solid electrolyte membrane of this invention has a porosity of not less than 20% to ensure that there are interconnected ion transport channels within the membrane. In some embodiments, the porosity of the solid electrolyte membrane is 22% to 40%, for example, 22%, 25%, 28%, 30%, 32%, 35%, 38%, or 40%. The porosity within the aforementioned range provides sufficient ion transport space while ensuring that the membrane has sufficient mechanical strength and compactness.
[0084] In some embodiments, the specific surface area of the solid electrolyte membrane is 100 m². 2 / g~220m 2 / g, for example, 100m 2 / g、110m 2 / g、120m 2 / g、148m 2 / g、152m 2 / g、168m 2 / g、175m 2 / g、183m 2 / g、198m 2 / g、206m 2 / g、215m 2 / g or 220m 2 / g. The specific surface area within the aforementioned range provides sufficient space for ion transport while ensuring that the membrane possesses adequate mechanical strength and density.
[0085] The porosity and specific surface area in this invention can be obtained by conventional testing methods in the art, including but not limited to calculations using gas adsorption methods (such as the BET method) combined with mercury intrusion porosimetry, for example, solid electrolyte membrane samples at 120°C and 10... -3 The adsorbate was completely removed after degassing in a high vacuum environment for 12 hours. Then, it was transferred to a low-temperature nitrogen adsorption instrument, and the nitrogen adsorption-desorption isotherm was tested at liquid nitrogen temperature of 77K. The relative pressure (P / P0) ranged from 0.01 to 0.99. The specific surface area was calculated by fitting the BET model in the range of P / P0=0.05-0.30. The pore size distribution was analyzed by the BJH model based on the desorption branch data. The porosity was calculated by the gas adsorption method.
[0086] In this invention, the thickness of the base film can be selected within a wide range, as long as the purpose of this invention can be achieved. In some embodiments, the thickness of the base film is 0.5mm to 1mm, for example, 0.5mm, 0.6mm, 0.7mm, 0.8mm, 0.9mm or 1mm.
[0087] In some embodiments, the buffer layer comprises at least one of Li3N, LLZO, and Al2O3. The buffer layer of the aforementioned materials can block electron penetration, avoid internal micro-short circuits, block carbon-based side reactions, isolate components such as binders from direct contact with the lithium anode, prevent the generation of harmful substances such as Li2CO3, and reduce interfacial impedance.
[0088] The thickness of the buffer layer in this invention can be selected within a wide range, as long as the purpose of this invention can be achieved. In some embodiments, the thickness of the buffer layer is 20nm~40nm, for example, 20nm, 25nm, 30nm, 35nm or 40nm.
[0089] As an example, the buffer layer includes Li3N. Li3N has superion conductivity and strong dendrite suppression capabilities, which can significantly increase the safe cycle life of the battery.
[0090] In this invention, the buffer layer can be disposed on one side of the base film along the thickness direction, or on both sides of the base film along the thickness direction. Preferably, it is disposed on the surface of the solid electrolyte membrane that is intended to contact the negative electrode of the battery, which can block the lithium dendrite growth path. The positive electrode itself is an electronic conductor, so a buffer layer is not required.
[0091] The thickness in this invention can be tested according to conventional testing methods in the art, including but not limited to measurement by a PPG thickness gauge.
[0092] In this invention, the inorganic framework comprises a porous silica-oxygenated inorganic framework material and a metal oxide. The porous silica-oxygenated inorganic framework material forms a three-dimensional framework to constitute the main network of the inorganic framework, and its abundant pores provide sufficient space for the wetting of the gel electrolyte and subsequent ion transport. The metal oxide particles are dispersed in the framework network or attached to the framework as functional additives, forming a more stable framework. In some embodiments, the porous silica-oxygenated inorganic framework material and the metal oxide are bonded by intermolecular forces (such as hydrogen bonds and van der Waals forces) to form an inorganic framework network. Furthermore, the presence of a binder helps to fix the metal oxide particles in the porous silica-oxygenated inorganic framework material.
[0093] In some embodiments, the mass ratio of the porous silica-oxygenated inorganic framework material to the metal oxide is (1.25~15):1, for example, 1.25:1, 1.5:1, 2:1, 3:1, 4:1, 5:1, 6.25:1, 7:1, 8:1, 9:1, 10:1, 12.5:1, 15:1, or any range of two of the above ratios. Controlling the mass ratio of the porous silica-oxygenated inorganic framework material to the metal oxide within the aforementioned range ensures that the inorganic framework provides sufficient porous structure to maintain ion transport channels. Simultaneously, the incorporation of an appropriate amount of metal oxide particles enhances mechanical support and regulates interfacial ion distribution, thereby synergistically optimizing the mechanical strength and ionic conductivity of the membrane.
[0094] In this invention, porous silica-oxygen inorganic framework materials refer to inorganic materials whose main components include silicon-oxygen bonds (Si-O) and have a porous structure. Their pore structure can originate from the inherent structure of natural minerals (such as the pores of biological remains in diatomaceous earth), or artificially synthesized mesoporous or macroporous structures. In some embodiments, porous silica-oxygen inorganic framework materials include at least one of diatomaceous earth, zeolite, mesoporous silica, and montmorillonite; all of the aforementioned materials have a Si-O-Si-based chemical structure and can obtain porous morphologies through natural or artificial means. The selection of the aforementioned types of porous silica-oxygen inorganic framework materials in this invention can provide high porosity and abundant ion transport channels for solid electrolyte membrane products.
[0095] As an example, porous silica-oxygenated inorganic framework materials preferably include diatomaceous earth. Further research has found that when porous silica-oxygenated inorganic framework materials contain diatomaceous earth, the overall performance of the solid electrolyte membrane is better. This is because diatomaceous earth naturally possesses high porosity, suitable and uniformly distributed pore size, and regular microstructure, which can significantly reduce raw material costs while ensuring the formation of efficient ion transport channels.
[0096] In this invention, metal oxides can promote interfacial ion migration and improve ionic conductivity. As long as the purpose of this invention can be achieved, there is no special limitation on the specific selection of metal oxides. In some embodiments, the metal oxides include at least one of ZnO, TiO2 and Al2O3.
[0097] As an example, metal oxides preferably include ZnO. Further research found that when the metal oxide contains ZnO, the overall performance of the solid electrolyte membrane is better. The reasons include: (1) Although TiO2 has a high dielectric constant (≈90), it has poor conductivity (i.e., it is an insulator), while ZnO is an n-type semiconductor that can assist electron transport. In addition, the polar surface of ZnO can adsorb Li⁺, which improves ion mobility; (2) Al2O3 is insulating and has high hardness, which can easily scratch the electrode, while ZnO has moderate hardness (Mohs hardness is 4), which is more compatible with the friction coefficient of porous silica-oxygen inorganic framework materials, especially diatomaceous earth.
[0098] In some embodiments, the inorganic framework has a mass content of 29% to 85% in the base membrane, for example, 29%, 32%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 77%, 79%, 80%, 84%, 85%, or any combination of two of the above values. Controlling the content of the inorganic framework within the aforementioned range can maintain the stability of the membrane structure while ensuring good ionic conductivity.
[0099] In this invention, the gel electrolyte comprises a flexible cross-linked polymer and a lithium salt, wherein the flexible cross-linked polymer provides a flexible medium, and the lithium salt is responsible for lithium ion dissociation and transport, and the two together serve as an ion-conducting medium.
[0100] In some embodiments, lithium salts are adsorbed onto a flexible cross-linked polymer to form an ion transport network. The lithium salts adsorbed onto the flexible cross-linked polymer are transported via chain segment movement or by transitions along polar groups.
[0101] In this invention, the flexible crosslinked polymer refers to a polymeric material capable of forming a three-dimensional network through inter-chain forces (such as hydrogen bonds, ionic bonds, and entanglement) or chemical bonds, and this network possesses a certain degree of flexibility and elasticity. Flexibility means that when the crosslinked network is subjected to external forces or small temperature fluctuations, it can undergo elastic deformation, buffer stress, and maintain structural integrity after deformation. In some embodiments, the flexible crosslinked polymer has a gel network structure composed of a natural polymeric backbone and a crosslinked phase. The natural polymeric backbone provides the main framework for gel formation and biocompatibility, while the crosslinked phase connects and reinforces the natural polymeric backbone through molecular chain entanglement or chemical crosslinking points, forming a stable flexible three-dimensional network. This flexible three-dimensional network coats inorganic particles, mitigating volume changes during charging and discharging. Furthermore, the gel network can be impregnated in the pores of a porous silica-oxygenated inorganic backbone material, achieving partial bonding through hydrogen bonds. Groups in lithium salts, such as LiTFSI, can also form ion-dipole interactions with the COC of the gel network, promoting ion diffusion.
[0102] The mass ratio of the natural polymer backbone to the crosslinked phase can be selected within a wide range, as long as the objective of this invention is achieved. In some embodiments, the mass ratio of the natural polymer backbone to the crosslinked phase is (0.5~7.5):1, for example, 0.5:1, 1:1, 1.5:1, 1.75:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 5.5:1, 6:1, 6.5:1, 7:1, 7.5:1, or any range of two of the above ratios, preferably (1~5):1. Controlling the mass ratio of the natural polymer backbone to the crosslinked phase within the aforementioned range can better achieve high ionic conductivity and structural stability of the gel electrolyte phase.
[0103] In some embodiments, the natural polymer backbone is formed from natural polymer materials. Examples of natural polymer materials include, but are not limited to, at least one of cellulose nanofibers, chitosan, and sodium alginate. These natural polymer materials are widely available, biodegradable, and rich in polar groups such as hydroxyl and carboxyl groups on their molecular chains, enabling them to form hydrogen bond networks and adsorb lithium ions.
[0104] As an example, cellulose nanofibers are a preferred natural polymer material. Cellulose nanofibers refer to high aspect ratio nanofibers, with diameters ranging from 5 nm to 60 nm and lengths reaching several micrometers, isolated from plant cell walls through mechanical / chemical treatment. Examples of cellulose nanofibers include TEMPO-oxidized cellulose nanofibers, carboxymethylated cellulose nanofibers, cationized cellulose nanofibers, and enzymatically hydrolyzed cellulose nanofibers. Using cellulose nanofibers as a natural polymer material offers advantages such as good biodegradability and the ability to form stable three-dimensional gel networks under mild conditions. This not only makes the preparation process more environmentally friendly but also facilitates the construction of uniform and continuous ion transport media, thereby better improving the ionic conductivity and structural stability of solid electrolyte membranes.
[0105] In some embodiments, the crosslinked phase is formed from a polymeric material having hydroxyl and / or carboxyl groups, including but not limited to at least one of polyvinyl alcohol (PVA), gelatin, carboxymethyl chitosan, and natural rubber. The aforementioned polymeric materials contain abundant polar groups, enabling them to form strong physical crosslinks (hydrogen bonds, etc.) with the natural polymeric backbone, thereby constructing a stable gel network.
[0106] As an example, polymeric materials having hydroxyl and / or carboxyl groups are preferably including, but not limited to, polyvinyl alcohol (PVA). Further research of the present invention found that when polymeric materials having hydroxyl and / or carboxyl groups contain polyvinyl alcohol (PVA), the overall performance of solid electrolyte membrane products is better. The reasons are: (1) Gelatin has poor thermal stability (low freezing point) and is prone to denaturation at high temperatures, while PVA has good heat resistance (melting point 230℃) and a stable structure after curing at room temperature; the solubility of carboxymethyl chitosan depends on pH value and requires an acidic environment, while PVA has wide water solubility (adaptable to pH values of 2~12) and is more widely applicable; (3) Natural rubber latex contains many impurities, which affects the purity of the electrode, while PVA has high purity (>99%) and its molecular weight can be controlled.
[0107] In this invention, the lithium salt can be any type of lithium salt commonly used in the art, as long as it achieves the purpose of this invention. In some embodiments, the lithium salt includes LiTFSI and / or LiPF6. LiTFSI, in particular, exhibits high thermal stability (decomposition temperature > 350°C) and high ionic conductivity (10⁻⁶ Ω·cm). -3 LiTFSI, with its better compatibility with cellulose nanofibers and superior hydrolysis resistance (S / cm), can be considered a preferred lithium salt. This allows LiTFSI to improve battery safety performance, avoid electrolyte failure caused by reactions, and form ion-dipole interactions with the COC of the gel network, promoting ion diffusion. LiTFSI is also compatible with high-nickel cathodes and generates no gas during high-temperature cycling.
[0108] The mass ratio of lithium salt to flexible crosslinked polymer has a certain influence on ionic conductivity. In order to better balance the carrier concentration and the stability of the gel network, in some embodiments, the mass ratio of lithium salt to flexible crosslinked polymer is (0.5~6):1, for example, 0.5:1, 1:1, 1.5:1, 1.82:1, 1.9:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, 5.5:1, 6:1, or any two of the above ratios, preferably (1.5~2):1.
[0109] In some embodiments, the mass content of the gel electrolyte in the base membrane is 5% to 67%, for example, 5%, 8%, 10%, 12%, 15%, 19%, 23%, 28%, 32%, 35%, 40%, 45%, 48%, 52%, 55%, 59%, 63%, 65%, 67%, or any combination of two of the above values. Controlling the content of the gel electrolyte within the aforementioned range ensures that the gel phase can form a continuous and interconnected ion transport network to provide high ionic conductivity, while avoiding insufficient mechanical support due to excessive gel content. Thus, it maintains the stability of the membrane structure while ensuring excellent ion transport performance.
[0110] In this invention, a binder is distributed between the inorganic framework and the gel electrolyte. The binder effectively bridges and tightly bonds the inorganic framework and the gel electrolyte, thereby enhancing the integrity and mechanical stability of the composite structure and reducing the transport resistance of ions at the interface.
[0111] In some embodiments, the binder includes at least one of sodium carboxymethyl cellulose (CMC) binder, polyacrylic acid (PAA) binder, polyvinyl alcohol (PVA) binder, and polyethylene oxide (PEO) binder. The aforementioned binder molecular chains contain polar groups such as carboxyl and hydroxyl groups. These polar groups are integrated into the inorganic framework of the porous silica-oxygen-containing inorganic framework material primarily through physical bonding and electrostatic interactions. The polar groups in the gel network form electrostatic attraction / hydrogen bonds, achieving mechanical bonding.
[0112] As an example, the binder includes sodium carboxymethyl cellulose (CMC) binder. The abundant carboxyl groups in CMC binder can form hydrogen bonds or electrostatic interactions with the silanol groups of the inorganic framework and the polar groups of the gel network, thereby effectively bridging and integrating the inorganic and gel phases, enhancing the integrity and mechanical stability of the composite structure, and reducing the interfacial ion transport resistance.
[0113] In some embodiments, the binder content in the base film is 1% to 15% by mass, for example, 1%, 1.45%, 2.3%, 2.7%, 3%, 4%, 5%, 6%, 8%, 10%, 12%, 15%, or any combination of two of the above values. Controlling the binder content within the aforementioned range ensures that sufficient binder integrates the inorganic framework and gel electrolyte to form a stable composite structure, while avoiding defects such as blockage of ion transport channels or increased interfacial impedance due to excessive binder. This ensures the ionic conductivity of the membrane while maintaining structural integrity.
[0114] In this invention, the base film further includes a conductive material. The inclusion of a conductive material in the base film can further improve ion migration efficiency and optimize interfacial charge distribution, thus constructing an auxiliary charge transport network.
[0115] In some embodiments, the conductive material is loaded onto a porous silica-oxygenated inorganic framework material to form a charge transport network. Furthermore, a binder assists in the uniform dispersion and adhesion of the conductive material to the surface of the porous silica-oxygenated inorganic framework material. The carbon-based conductive material loaded onto the porous silica-oxygenated inorganic framework material and the metal oxide particles can synergistically construct an electron / ion dual continuous transport channel. By adjusting the local ion concentration and electric field distribution, interfacial polarization is effectively reduced, and rate performance is improved.
[0116] In some embodiments, the conductive material has C=O groups. Conductive materials with C=O groups can provide active sites, promoting ion adsorption and interfacial interaction. Furthermore, the C=O groups in the conductive material are hydrogen-bonded to the Si-O-Si in the porous silica-oxygenated inorganic framework. This hydrogen bonding enhances the interfacial bonding between the conductive material and the inorganic framework, resulting in a more uniform and robust distribution of the electron conduction network in the base film, thereby improving charge transport efficiency and the overall electrochemical stability of the structure.
[0117] In some embodiments, the conductive material includes a carbon-based conductive material. The carbon-based conductive material may include, but is not limited to, at least one of graphene quantum dots (GQDs), multi-walled carbon nanotubes (MWNTs), and graphene oxide (GO).
[0118] As an example, carbon-based conductive materials include graphene quantum dots (GQDs). Further research has found that solid electrolyte membranes exhibit better overall performance when carbon-based conductive materials contain GQDs. This is due to several factors: GQDs possess a high specific surface area, which increases the density of electron conduction pathways; they form hydrogen-bonded networks with porous silica-based inorganic framework materials, stabilizing the composite structure; and they have excellent dispersion capabilities, preventing material aggregation and channel blockage. While multi-walled carbon nanotubes (MWNTs) exhibit excellent conductivity, they are prone to aggregation and require high-temperature processing. Graphene oxide (GO) requires reduction treatment (such as thermal or chemical reduction), which may introduce impurities.
[0119] In some embodiments, the mass ratio of the conductive material to the porous silica-oxygenated inorganic framework material is 1:(8~10), for example, 1:8, 1:9, or 1:10. Controlling the ratio of the conductive material to the porous silica-oxygenated inorganic framework material within the aforementioned range can both form a continuous electron conduction network to promote charge transport and avoid excessive conductive material from blocking ion transport channels or compromising structural integrity, thereby better optimizing the synergy of electron and ion transport.
[0120] In this invention, the aforementioned conductive material can synergistically form an electron / ion dual continuous channel with metal oxides. Metal oxides, especially ZnO polar surfaces, adsorb Li... + The formation of local high-concentration regions allows the conductive material to provide electron transition nodes, enabling ion / electron coupling transport. During charging and discharging, the interfacial polarization voltage decreases, significantly improving rate performance. The conductive material works synergistically with the buffer layer and porous framework. The buffer layer fills the pores on the surface of the porous silica-oxygen inorganic framework material and covers the active sites at the edges of the conductive material, thereby eliminating interfacial defects. The electron conduction path of the conductive material is confined within the electrolyte, preventing electrons from penetrating into the negative electrode. After cycling, interfacial byproducts are significantly reduced.
[0121] In some embodiments of the present invention, a method for preparing a solid electrolyte membrane is also provided, comprising the following steps: a) A slurry containing a porous silica-oxygenated inorganic framework material is first mixed with a solution containing a gel precursor, a lithium salt, and a crosslinking agent to obtain a mixed slurry; then the mixed slurry is spray-dried to obtain an intermediate. b) The intermediate obtained in step a) and the metal oxide are ball-milled to obtain ball milling material; then, in the presence of water, the binder and the ball milling material are mixed for the second time, and then successively molded and dried to obtain a base film; c) Deposit a buffer material onto the base film obtained in step b) to form a buffer layer, thereby obtaining a solid electrolyte membrane.
[0122] The solid electrolyte membrane prepared by the preparation method of the present invention includes a base membrane and a buffer layer disposed on at least one side surface of the base membrane along the thickness direction; the porosity of the solid electrolyte membrane is not less than 20%, the base membrane includes an inorganic framework, a gel electrolyte and a binder, the inorganic framework includes porous silica-oxygenated inorganic framework materials and metal oxides, and the gel electrolyte includes a flexible cross-linked polymer and a lithium salt.
[0123] In the preparation method of this invention, when a solution containing lithium salt, gel precursor, and crosslinking agent is mixed with a slurry containing porous silica-oxygenated inorganic framework material, the solution can penetrate into the micron- and nano-scale pores of the framework under capillary force. During subsequent mild drying (such as spray drying) and crosslinking curing reactions, the polymer components (gel precursor and crosslinking agent) in the solution form a crosslinked network inside and on the surface of the framework pores, while simultaneously encapsulating and fixing the lithium salt to form a gel electrolyte. Subsequently, the cured gel network partially bonds with the inorganic framework, which serves as a template and support, through forces such as hydrogen bonds, thereby forming a three-dimensional interpenetrating network structure in which the inorganic framework network and the gel network interweave and interlock at the microscopic level. This structure allows ion transport channels to be continuous and interconnected in three-dimensional space, significantly reducing the tortuosity of the ion transport path and the diffusion barrier.
[0124] In addition, the method for preparing the solid electrolyte membrane of the present invention can reduce production costs, achieve environmentally friendly preparation, and is compatible with production lines, adding only a deposition step, and has high roll-to-roll production speed and efficiency.
[0125] It should be understood that all the features and advantages described above for the solid electrolyte membrane also apply to the preparation method of the solid electrolyte membrane, and will not be repeated here.
[0126] In this invention, the slurry containing porous silica-oxygenated inorganic framework materials refers to a slurry formed by dispersing the porous silica-oxygenated inorganic framework materials and other components in a solvent. This solvent can be a conventional solvent in the art, including but not limited to ethanol. Specifically, the porous silica-oxygenated inorganic framework materials and other components are dispersed in ethanol to form a slurry. The dispersion method is not particularly limited, and may include, but is not limited to, ultrasonic dispersion and / or mechanical stirring. The ultrasonic dispersion power can be 300W~500W, and mechanical stirring can be performed at room temperature for 8h-24h at a stirring speed of 300rpm~700rpm. The amount of solvent used, i.e., the solid content of the slurry, is not particularly limited, as long as it ensures uniform dispersion of the porous silica-oxygenated inorganic framework materials and other components.
[0127] In some embodiments, the porosity of the porous silica-oxygenated inorganic framework material is >90%. This high-porosity porous silica-oxygenated inorganic framework material can increase the specific surface area and internal space of the subsequent inorganic framework, providing a sufficient three-dimensional carrier for the subsequent loading of gel electrolytes and lithium salts, thereby enabling the formation of continuous and efficient ion transport channels.
[0128] In some embodiments, the pore size distribution (PDI) of the porous silica-oxygenated inorganic framework material is 0.6–0.75, for example, 0.6, 0.63, 0.65, 0.68, 0.7, 0.72, or 0.75. This PDI range indicates that the pore size distribution of the porous silica-oxygenated inorganic framework material is relatively concentrated, which is beneficial for the uniform filling and stable shaping of the gel electrolyte during the drying process, thereby reducing structural defects caused by uneven local capillary stress and forming a more uniform ion transport path.
[0129] In this invention, PDI refers to the relative width index of aperture distribution, PDI = (Dv) / ( ... 90 -Dv 10 ) / Dv 50 Among them, Dv 10 Dv 50 Dv 90 As is known in the art, Dv 10 Dv 50 Dv 90 This refers to the pore size values corresponding to 10%, 50%, and 90% of the volume on the cumulative diameter distribution curve of a material, which can be determined using instruments and methods known in the art. For example, the pore size distribution curve can be calculated based on the Barrett-Joyner-Halenda (BJH) desorption support model. Wherein, Dv... 90 Dv represents the pore diameter value corresponding to when the cumulative pore volume reaches 90% of the total pore volume on the cumulative pore volume distribution curve. 50 Dv represents the pore diameter value corresponding to when the cumulative pore volume reaches 50% of the total pore volume on the cumulative pore volume distribution curve. 10 The cumulative pore volume distribution curve represents the pore size value corresponding to when the cumulative pore volume reaches 10% of the total pore volume; its matrix generally contains macropores (1μm~10μm), mesopores (2nm~50nm) and micropores (<2nm).
[0130] In some embodiments, the surface roughness Ra of the porous silica-oxygenated inorganic framework material is 50 nm to 200 nm, for example, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 120 nm, 130 nm, 150 nm, 160 nm, 180 nm or 200 nm.
[0131] In this invention, surface roughness refers to the unevenness of the surface of the porous silica-oxygenated inorganic framework material, characterized by small spacing and minute peaks and valleys. It can be measured using conventional methods in the field of this invention, including but not limited to the arithmetic mean deviation Ra of the profile specified in GB / T1031-2009. The aforementioned surface roughness range can increase the contact area and mechanical interlocking effect between the inorganic framework and the gel electrolyte, thereby significantly improving the interfacial bonding strength between them, which is beneficial for enhancing the stability of the composite structure and reducing interfacial ion transport resistance.
[0132] In some embodiments, the porous silica-oxygenated inorganic framework material includes at least one of diatomaceous earth, zeolite, mesoporous silica, and montmorillonite, preferably diatomaceous earth. Further research has found that the reasons for the preference of diatomaceous earth include: (1) Although the porosity of zeolite is >85%, the regularity of the pore structure is low, while the natural porous structure of diatomaceous earth is easier to achieve a porosity >90% after artificial processing; (2) Mesoporous silica requires chemical synthesis, which is costly and has a narrow pore size distribution, while diatomaceous earth is a natural raw material with a wide pore size distribution (micrometer-nanometer level), which is conducive to ion transport; (3) Montmorillonite has a layered structure that is prone to agglomeration and requires additional dispersants; while diatomaceous earth has a high surface roughness and a stronger interfacial bond when combined with other components.
[0133] In this invention, the size of the porous silica-oxygenated inorganic framework material can be selected within a wide range, as long as the purpose of this invention can be achieved. In some embodiments, the particle size of the porous silica-oxygenated inorganic framework material is 10 μm to 100 μm.
[0134] To ensure that the inorganic framework provides superior ion transport channels and loading capacity, in some embodiments, the porous silica-oxygenated inorganic framework material may be selected as an activated porous silica-oxygenated inorganic framework material. Activation treatment refers to the process of treating the porous silica-oxygenated inorganic framework material raw material to improve its purity, specific surface area, porosity, and surface activity. As long as the objectives of this invention are achieved, the activation treatment method can be a conventional method in the art, including but not limited to acid treatment and calcination. As an example, the porous silica-oxygenated inorganic framework material includes porous silica-oxygenated inorganic framework material that has undergone acid treatment, washing, drying, and calcination.
[0135] In some embodiments, the acid treatment conditions include microwave pickling in the presence of dilute hydrochloric acid. Acid treatment can effectively remove inherent metal oxide impurities such as Fe and Al from porous silica-based inorganic framework materials and clear pores. The dilute hydrochloric acid generally refers to an aqueous solution with a molar concentration not exceeding 6 mol / L. As an example, the microwave pickling power can be 300W~500W, the microwave pickling time can be 30min~60min, and the microwave frequency can be 2GHz~3GHz.
[0136] There are no special restrictions on the amount of dilute hydrochloric acid used during acid treatment, as long as the acid solution can be used to ensure uniform penetration of the porous silica-oxygenated inorganic framework material.
[0137] The above washing mainly involves washing the solid phase obtained after acid treatment, that is, the porous silica-oxygenated inorganic framework material after acid treatment is filtered and washed with water until the filtrate is neutral, preferably deionized water.
[0138] The purpose of the above drying is to remove water. The drying method can be a conventional method in the field, such as atmospheric pressure drying or vacuum drying, for example, drying at 60~100℃ for 8h~16h.
[0139] In some embodiments, the calcination conditions include being carried out under an inert atmosphere. The inert atmosphere includes at least one of a nitrogen atmosphere or a gas atmosphere of a group 0 element of the periodic table, such as a nitrogen atmosphere.
[0140] In some embodiments, the calcination conditions include a temperature of 600°C to 800°C. In this invention, the temperature can be increased to 600°C to 800°C at a certain heating rate, for example, a heating rate of 3°C / min to 8°C / min.
[0141] In some embodiments, the calcination conditions include a time of 1 to 3 hours. The aforementioned time is calculated from the point after the temperature is raised to the point of calcination.
[0142] As an example, the activation of porous silica-oxygenated inorganic framework materials includes: weighing the porous silica-oxygenated inorganic framework material and placing it in a polytetrafluoroethylene (PTFE) reactor; preparing a certain amount of dilute HCl solution and adding it to the PTFE reactor; performing microwave-assisted acid washing; placing the PTFE reactor in a microwave reactor; setting the microwave power to 300W~500W, the microwave time to 30min~60min, and the microwave frequency to 2GHz~3GHz to ensure that the acid solution uniformly penetrates the pores of the porous silica-oxygenated inorganic framework material to remove surface impurities (such as oxides of Fe and Al); filtering the porous silica-oxygenated inorganic framework material after acid washing; washing it with deionized water until neutral (washing solution pH value is 7); drying it at 60~100℃ for 8h~16h; then transferring it to a tube furnace and heating it at 3℃ / min~8℃ / min to 600℃~800℃, holding it at that temperature for 1h~3h (under inert atmosphere protection); and naturally cooling it to room temperature to obtain the activated porous silica-oxygenated inorganic framework material. Specifically, the porous silica-oxygenated inorganic framework material preferably uses the aforementioned activated material, which has a porosity > 90%, a surface roughness Ra of 50 nm to 200 nm, and a pore size PDI of 0.6 to 0.75.
[0143] In this invention, the solution containing the gel precursor, lithium salt, and crosslinking agent refers to a solution formed by dissolving the gel precursor, lithium salt, and crosslinking agent in a good solvent, which is generally water, preferably deionized water. The gel precursor, lithium salt, and crosslinking agent can be added to water simultaneously to form corresponding solutions, or the gel precursor, lithium salt, and crosslinking agent can be dissolved separately in water to obtain an aqueous solution of the gel precursor, a lithium salt solution, and a crosslinking agent solution, respectively. The aqueous solution of the gel precursor, the lithium salt solution, and the crosslinking agent solution are then added to a slurry containing a porous silica-oxygenated inorganic framework material for a first mixing.
[0144] In some embodiments, the solid content of the mixed slurry is 10% to 30%, for example, 10%, 12%, 15%, 18%, 20%, 23%, 25%, 28%, or 30%. Controlling the solid content of the mixed slurry within the aforementioned range allows for a balance between the efficiency of spray drying and the final particle morphology. In this invention, the final solid content of the mixed slurry can be controlled by controlling the solid content of the slurry containing the porous silica-oxygenated inorganic framework material and the solvent content in the solution containing the gel precursor, lithium salt, and crosslinking agent.
[0145] The present invention does not impose any special restrictions on the conditions for the first mixing, as long as the solution fully wets the pores of the skeleton. In some embodiments, the conditions for the first mixing include stirring at room temperature for 18 to 30 hours.
[0146] In some embodiments, the spray drying conditions include: an inlet air temperature of 80°C to 100°C, an outlet temperature of 60°C to 70°C, an atomization pressure of 0.2 MPa to 0.3 MPa, and a feed rate of 30 mL / min to 40 mL / min. Controlling the spray drying conditions within the aforementioned range allows the droplets to dry instantaneously, and the internal solvent to evaporate rapidly, forming pores, resulting in Dv. 50 Intermediate particles with a particle size of 5 μm to 10 μm. That is, in some embodiments, the Dv of the intermediate... 50 The particle size is 5μm~10μm.
[0147] To avoid the influence of residual moisture in the intermediate on subsequent steps, in some embodiments, the preparation method further includes: in step a), vacuum drying after spray drying to make the moisture content of the intermediate <0.5wt%. The conditions for vacuum drying may include, but are not limited to: a temperature of 60℃~100℃ and a time of 1h~3h.
[0148] As an example, the preparation steps of the intermediate include: (1) Weigh lithium salt and dissolve it in deionized water, and stir until completely dissolved to obtain lithium salt solution; disperse cellulose nanofiber aqueous solution by high pressure homogenizer to eliminate agglomeration; dissolve crosslinking agent in 50 mL of deionized water to obtain crosslinking agent solution; slowly add lithium salt solution, cellulose nanofiber aqueous solution and crosslinking agent solution to porous silica-oxygenated inorganic framework material, control the total solid content at 10%~30%, and stir at room temperature for 18h~30h using planetary mixer to ensure that lithium salt is uniformly dispersed in cellulose network to construct gel electrolyte, and finally stir to obtain mixture; (2) The above mixture is placed in a spray drying tower with an inlet air temperature of 80℃~100℃, an outlet temperature of 60℃~70℃, an atomization pressure of 0.2MPa~0.3MPa, and a feed rate of 30mL / min~40mL / min. The particle size Dv after drying is... 50 =5μm~10μm, collect the dried particles, dehumidify in a vacuum drying oven at 60℃~100℃ for 1h~3h, the moisture content is <0.5wt%, and the intermediate is obtained.
[0149] In some embodiments, the gel precursor comprises a natural polymer material, which includes at least one of cellulose nanofibers, chitosan, and sodium alginate, preferably cellulose nanofibers. Further research of the present invention has found that when the natural polymer material contains cellulose nanofibers, the overall performance of the solid electrolyte membrane product is better. The reasons include: (1) Chitosan requires acidic conditions to dissolve, and its antibacterial properties may introduce impurities, while cellulose nanofibers can be dispersed under neutral conditions and have better biodegradability; (2) Sodium alginate requires calcium ion crosslinking and curing, which is a complex process, while cellulose nanofibers can be directly cured by PVA crosslinking agent, which simplifies the process.
[0150] In some embodiments, the crosslinking agent comprises a polymeric material having hydroxyl and / or carboxyl groups. The hydroxyl or carboxyl groups in the crosslinking agent can form numerous hydrogen bonds or ion-dipole interactions with the gel precursor (such as cellulose nanofibers), thereby constructing a more stable and uniform three-dimensional crosslinked network, effectively improving the mechanical strength and structural integrity of the gel electrolyte.
[0151] In this invention, the molecular weight of the crosslinking agent can be selected within a wide range, as long as the objective of the invention is achieved. Generally, when the molecular weight of the crosslinking agent is too low, it leads to insufficient crosslinking density, low gel strength, and a high risk of cold-pressing cracking. When the molecular weight of the crosslinking agent is too high, the dissolution temperature is high, energy consumption increases, and the viscosity is too high, easily causing uneven dispersion. In some embodiments, the average molecular weight of the crosslinking agent is 85,000 g / mol to 130,000 g / mol. Controlling the average molecular weight of the crosslinking agent within the aforementioned range can better improve the mechanical strength and structural integrity of the gel electrolyte.
[0152] Furthermore, in this invention, the crosslinking agent and the binder can be cured synergistically. The crosslinking agent enables the molecular chains to entangle, and the binder can construct a hydrogen bond network, thereby achieving a mechanical-chemical double crosslinking structure. Ultimately, this significantly improves the tensile strength of the solid electrolyte membrane, inhibits lithium dendrite puncture, and makes it structurally stable at high temperatures with low thermal shrinkage.
[0153] In some embodiments, the mass ratio of the porous silica-oxygenated inorganic framework material to the gel precursor is (5~45):(1.5~7.5). Within this range, common intermediate ratios include, but are not limited to, 10:3, 15:3, 20:3, 25:3, 30:3, 35:3, 40:3, 45:3 (15:1), 10:4.5, 20:4.5, 30:4.5, 40:4.5, 10:6, 20:6, 30:6, 40:6, 20:7.5, 30:7.5, 40:7.5, 45:7.5, etc.
[0154] In some embodiments, the mass ratio of the gel precursor to the lithium salt is (1.5~7.5):(5~15). Within this range, common intermediate ratios include, but are not limited to, 1.5:5, 1.5:10, 3:5, 3:10, 3:15, 4.5:5, 4.5:10, 4.5:15, 6:5, 6:10, 6:15, 7.5:10, 7.5:12.5, 7.5:15, 3:12.5, 4.5:12.5, 6:12.5, etc.
[0155] In some embodiments, the mass ratio of the gel precursor to the crosslinking agent is (1.5~7.5):(1~3). Within this range, common intermediate ratios include, but are not limited to, 1.5:3, 1.5:2, 1.5:1.5, 4.5:4, 3:2, 4.5:2, 5:2, 3:1, 7.5:2, 4.5:1, 6:1, 7.5:1, etc.
[0156] In some embodiments, the metal oxide includes at least one of ZnO, TiO2, and Al2O3. Its particle size is preferably 10 nm to 50 nm, for example, 35 nm ZnO nanoparticles.
[0157] In some embodiments, in step b), ball milling is preferably wet ball milling. The ball-to-powder ratio (mass ratio) can be (1~20):1, and the ball milling medium can be acetone or ethanol, for example, 30%~50% by volume of ethanol can be added to the mixed powder. Specifically, the metal oxide can be first dispersed in the ball milling medium, preferably ultrasonically dispersed in the ball milling medium, and then the intermediate is added for ball milling.
[0158] In some embodiments, the conditions for wet ball milling may include: a rotation speed of 200 rpm to 500 rpm and a time of 1 h to 3 h. The aforementioned ball milling can ensure that the metal oxide nanoparticles are uniformly dispersed and adhere to the surface of the intermediate particles.
[0159] In some embodiments, after ball milling, a binder aqueous solution (such as a CMC aqueous solution) may be added for a second mixing. There are no particular limitations on the concentration of the binder aqueous solution; for example, the concentration may be 0.5 wt% to 5 wt%.
[0160] In some embodiments, the conditions for the second mixing include stirring at room temperature for 0.5 h to 2 h.
[0161] In some embodiments, the molding process is cold pressing. The cold pressing process allows for close contact between particles, enabling the binder to form bonding bridges, ultimately resulting in a base film with a porosity of not less than 20% after drying. In some embodiments, the cold pressing conditions include: a temperature preferably of 20°C to 30°C, a pressure preferably of 10 MPa to 20 MPa, and a time preferably of 1 min to 10 min. The aforementioned pressure is the main pressure; a pre-pressure of 2 MPa to 8 MPa can be set before applying the main pressure.
[0162] In this invention, the drying in step b) can be a conventional drying method in the art, including but not limited to vacuum drying, such as vacuum drying at 80°C to 160°C for 1 to 3 hours.
[0163] In some embodiments, the mass ratio of porous silica-oxygenated inorganic framework material to metal oxide is (2~20):(1~8). Within this range, common intermediate ratios include, but are not limited to, 1:4, 1:3, 1:2, 2:3, 3:4, 1:1, 5:4, 4:3, 3:2, 7:4, 2:1, 9:4, 5:2, 3:1, 7:2, 4:1, 9:2, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 12:1, 14:1, 16:1, 18:1, and 20:1. In this invention, controlling the mass ratio of porous silica-oxygenated inorganic framework material to metal oxide within the aforementioned range allows the metal oxide to function as an effective structural filler and functional additive, appropriately embedding itself in the pores of the inorganic framework or adhering to its surface. This maintains the overall porous structure of the base film to ensure ion transport while enhancing its mechanical support and structural density.
[0164] As an example, metal oxides are dispersed in ethanol, ultrasonically treated for a period of time, and then an intermediate is added. The mixture is then ball-milled (200 rpm to 500 rpm, ball-to-material ratio (1 to 20): 1) for 1 to 3 hours to ensure that the metal oxides and the intermediate are fully mixed to obtain the ball milling material. The binder is dissolved in deionized water (stirred at 50°C to 80°C until transparent) and slowly added to the aforementioned ball milling material. The mixture is stirred for 0.5 to 2 hours to obtain the base film material. The base film material is then cold-pressed at 20°C to 30°C using a stainless steel mold. The pre-pressing pressure is 2 MPa to 8 MPa, and the main pressure is 10 MPa to 20 MPa (hydraulic press, holding pressure for 1 to 10 minutes). The cold-pressed tablets are then dried in a vacuum drying oven (80°C to 160°C, vacuum degree < 0.1 Pa) for 1 to 3 hours to obtain the base film.
[0165] In some embodiments, the binder includes at least one of sodium carboxymethyl cellulose (CMC) binder, polyacrylic acid (PAA) binder, polyvinyl alcohol (PVA) binder, and polyethylene oxide (PEO) binder. Preferably, when the binder contains sodium carboxymethyl cellulose (CMC) binder, the overall performance of the solid electrolyte membrane is better. The reasons include: (1) PAA binder is prone to corrosion of the electrode in a strongly acidic environment, while CMC binder can form a strong hydrogen bond network under neutral conditions; (2) PVA binder has poor solubility (requires high temperature) and competes with cellulose nanofibers for crosslinking sites, while the viscosity of CMC binder is controllable and the particle dispersion can be adjusted; (3) PEO binder has high crystallinity and low ionic conductivity, while CMC binder has better flexibility after film formation and excellent self-healing ability of hydrogen bond network. Cracks can self-heal during charging and discharging, which can improve the integrity of electrode materials.
[0166] In some embodiments, the mass ratio of porous silica-oxygenated inorganic framework material to binder is (10~60):(1~3). Common intermediate ratios within this range include, but are not limited to, 10:3, 15:3, 20:3, 15:2, 25:3, 10:1, 35:3, 25:2, 40:3, 15:1, 50:3, 35:2, 55:3, 20:1, 45:2, 25:1, 55:2, 30:1, 35:1, 40:1, 45:1, 50:1, 55:1, and 60:1. In this invention, controlling the mass ratio of porous silica-oxygenated inorganic framework material to binder within the aforementioned range ensures sufficient wetting and encapsulation of the inorganic framework particles to form a stable composite matrix, while preventing excessive amounts from clogging the inherent porous structure of the inorganic framework. This allows for the enhancement of the overall mechanical integrity of the prepared base film while maintaining the effectiveness of ion transport channels.
[0167] In this invention, based on the composite membrane structure with ion transport channels and mechanical support, the base membrane may further include a conductive material to further improve ion migration efficiency and optimize interfacial charge distribution. In solid electrolyte membrane products, the conductive material is preferably loaded onto a porous silica-oxygenated inorganic framework material, forming a charge transport network tightly bonded to the inorganic framework. There are various ways to load the conductive material. Specifically, the timing of introducing the conductive material can be varied. For example, the conductive material (such as graphene quantum dots GQDs) can be dispersed in a solvent and then stirred together with the porous silica-oxygenated inorganic framework material (such as activated porous silica-oxygenated inorganic framework material), relying on physical adsorption and possible chemical interactions (such as hydrogen bonding) to adhere it to the framework surface and pores. Alternatively, the conductive material can be introduced during ball milling, allowing it to be ball-milled with the intermediate and metal oxide obtained in step a). That is, in some embodiments, the slurry including the porous silica-oxygenated inorganic framework material also includes the conductive material, and / or the conductive material is added during the ball milling process. Regardless of the method, the mass ratio of conductive material to porous silica-oxygenated inorganic framework material is preferably controlled at 1:(8~10).
[0168] As an example, a method for preparing a slurry containing a porous silica-oxygenated inorganic framework material includes: Weigh out the conductive material and disperse it in ethanol, then sonicate it for 10-60 minutes (power 300W-500W, frequency 30kHz-50kHz); then add the activated porous silica-oxygen inorganic framework material and mechanically stir at room temperature (speed 300rpm-700rpm) for 8-24 hours to form a uniform porous silica-oxygen inorganic framework / conductive material.
[0169] The present invention does not specifically limit the deposition method in step c), as long as it achieves the purpose of the invention. In some embodiments, in step c), the deposition is performed by chemical vapor deposition (such as magnetron sputtering). The buffer material may include at least one of Li3N, LLZO, and Al2O3.
[0170] In some embodiments, the substrate temperature is 100°C to 300°C, and the sputtering power is 0.1 kW / cm². 2 ~1kW / cm 2 The working gas is an inert gas, the deposition working pressure is 0.2 Pa to 1.5 Pa, and the deposition time is 10 min to 30 min. By controlling the deposition parameters, a dense buffer layer with a thickness of 20 nm to 40 nm can be obtained on the surface of the base film.
[0171] Using the above preparation method, a composite solid electrolyte membrane with a three-dimensional interpenetrating network structure can be constructed at a process temperature not exceeding 300℃ (the main process temperature is room temperature to 200℃). The entire method has clear steps and mild conditions, avoiding the damage to the porous structure and heat-sensitive components caused by high-temperature sintering. At the same time, through the synergistic use of spray drying, ball milling, and cold pressing, the final porosity, component dispersion, and interface structure of the membrane are precisely controlled, thereby ensuring the repeatability and superiority of the product performance.
[0172] The solid electrolyte membrane of the present invention can be used to assemble batteries. In some embodiments, the present invention provides a battery including a positive electrode, a negative electrode, and a solid electrolyte membrane disposed between the positive electrode and the negative electrode; the solid electrolyte membrane includes the solid electrolyte membrane provided in any of the above embodiments or the solid electrolyte membrane prepared by the preparation method of the solid electrolyte membrane provided in any of the above embodiments.
[0173] During assembly, the solid electrolyte membrane can be cut and stacked with the electrode sheet. Hot or cold pressing is used to ensure tight interfacial contact, followed by encapsulation into a pouch cell or button cell. Batteries assembled using the solid electrolyte membrane of this invention combine excellent rate performance due to high ionic conductivity, anti-dendritic ability due to high mechanical strength, and high interfacial stability due to the buffer layer, thereby achieving high safety and long cycle life. In some embodiments, the surface of the buffer layer in the solid electrolyte membrane is in direct contact with the negative electrode sheet.
[0174] The present invention will be specifically described below with reference to the accompanying drawings and embodiments. However, the implementation and protection of the present invention are not limited thereto. The following embodiments are only some embodiments of the present invention and are not intended to limit the present invention. Where specific techniques or conditions are not specified in the embodiments, they shall be performed in accordance with the techniques or conditions described in the literature in this field or in accordance with the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be obtained commercially.
[0175] In the following examples and comparative examples: The cellulose nanofibers in the aqueous solution are TOCN (TEMPO oxidized cellulose nanofibers), with a diameter range of 3~10nm, and are manufactured by Exilva P-01-V and Borregaard AS.
[0176] The moisture content was determined by the oven constant weight method according to GB / T 2679.2-2015. The weighing dish m0 was dried to constant weight, and the sample + dish weight m1 was dried at 105℃ to constant weight m2. W (%) = m1-m2 / m1-m0 × 100%.
[0177] Aperture PDI = (Dv) 90 -Dv 10 ) / Dv 50Based on the Barrett-Joyner-Halenda (BJH) desorption support model, the pore size distribution curve was calculated. Wherein, Dv 90 Dv represents the pore diameter value corresponding to when the cumulative pore volume reaches 90% of the total pore volume on the cumulative pore volume distribution curve. 50 Dv represents the pore diameter value corresponding to when the cumulative pore volume reaches 50% of the total pore volume on the cumulative pore volume distribution curve. 10 This represents the pore diameter value corresponding to when the cumulative pore volume reaches 10% of the total pore volume on the cumulative pore volume distribution curve.
[0178] Surface roughness was obtained by testing the arithmetic mean deviation Ra of the profile as specified in GB / T1031-2009. The sampling length lr was 0.8 mm; the evaluation length ln = 5 × lr = 4 mm; the stylus tip radius was 2 μm; and the measurement rate was 0.5 mm / s. Two working surfaces, the base film Rohm and the Li3N sputtering pattern layer, were tested separately, with 5 random measurement points per sample. .
[0179] The thickness was obtained by testing with a PPG thickness gauge. The arithmetic mean was taken by measuring the thickness at 6 random points (four corners + center + side) three times.
[0180] Example 1 Preparation of solid electrolyte membranes: S1: Raw Materials and Pretreatment: 1. Activation of diatomaceous earth: Weigh 90g of diatomaceous earth (SiO2 content >95%, average particle size 25μm, pore size PDI=0.73, surface roughness Ra=80nm), place it in a polytetrafluoroethylene (PTFE) reactor, prepare 200mL of dilute HCl solution (2mol / L), add it to the PTFE reactor, perform microwave-assisted acid washing, place the PTFE reactor in a microwave reactor, set the microwave power to 400W, microwave time to 45min, and microwave frequency to [missing value]. At 2.45 GHz, the acid solution was used to ensure uniform penetration into the pores of the diatomaceous earth to remove surface impurities (such as oxides of Fe and Al). After acid washing, the diatomaceous earth was filtered, washed with deionized water until neutral (the washing solution pH was 7), and dried at 80°C for 12 hours. Then, it was transferred to a tube furnace and heated to 700°C at a rate of 5°C / min, held at that temperature for 2 hours (under N2 protection), and naturally cooled to room temperature to obtain activated diatomaceous earth. The activated diatomaceous earth had a pore size PDI of 0.67 and a surface roughness Ra of 150 nm.
[0181] Scanning electron microscopy (SEM) image of diatomaceous earth as shown below Figure 1 As shown. (Through) Figure 1 Diatomaceous earth exhibits a porous structure and can be used for Li + The transmission provides an effective transmission path.
[0182] 2. Conductive material composite: Weigh 10g of graphene quantum dots (GQDs, average particle size 6nm) and disperse them in 50mL of ethanol. Sonicate for 30min (power 200W, frequency 40kHz). Then add the activated diatomaceous earth (90g) and mechanically stir (500rpm) for 12h to form a uniform diatomaceous earth / GQDs composite slurry.
[0183] S2: Preparation of intermediates: 1. Raw material mixing: Weigh 10g of LiTFSI and dissolve it in 120mL of deionized water, stirring until completely dissolved to obtain a LiTFSI solution; disperse 350mL of cellulose nanofiber aqueous solution (concentration 1wt%) using a high-pressure homogenizer (pressure 250bar) to eliminate agglomeration; dissolve 2g of PVA crosslinking agent (average molecular weight 95000g / mol) in 50mL of deionized water (stirred in an 80℃ water bath until transparent) to obtain a PVA solution; slowly add the LiTFSI solution, cellulose nanofiber aqueous solution, and PVA solution to the above diatomaceous earth / GQDs composite slurry, and stir at room temperature for 24h using a planetary mixer (speed 35rpm) to ensure that LiTFSI is uniformly dispersed in the cellulose network to construct the gel electrolyte, and finally stir to obtain a mixture.
[0184] 2. Spray Drying: Place the above mixture in a spray drying tower with an inlet air temperature of 90℃, an outlet temperature of 65℃, and an atomization pressure of 0.25MPa (two-fluid nozzle). The feed rate is 35mL / min, and the particle size Dv after drying is... 50 =7.5μm, collect dried particles, dehumidify in a vacuum drying oven at 80℃ for 2h, moisture content <0.5wt%.
[0185] S3: Mechanical mixing and cold pressing: 1. Dispersion of metal oxide nanoparticles: Weigh 5g of ZnO nanoparticles (35nm particle size) and disperse them in 50mL of ethanol. Sonicate for 30min. Add the dried particles (80g) collected by spray drying. Ball mill the particles (400rpm) for 2h to ensure that ZnO and dried particles are fully mixed to obtain the ball milling material. Dissolve 2g of CMC binder in 50mL of deionized water (stir at 60℃ until transparent) and slowly add it to the ball milling material. Stir for 1h to obtain the base film material.
[0186] 2. Cold pressing: The base film material is cold pressed at 25℃ using a stainless steel mold (diameter 10mm, height 0.75mm), with a pre-press pressure of 5MPa and a main pressure of 15MPa (hydraulic press, holding pressure for 5min). The cold-pressed sheet is dried in a vacuum drying oven (120℃, vacuum degree <0.1Pa) for 2h to obtain a base film with a thickness of 0.752mm.
[0187] S4: Li3N sputtering deposition: The base film obtained by the above cold pressing molding was placed in a magnetron sputtering device, using high-purity Li3N (99.99% purity) as the target material, a substrate temperature of 200℃, and a sputtering power of 0.5kW / cm². 2 The working pressure was 0.8 Pa (Ar:N2=4:1, volume ratio), the deposition time was 20 min, and a 30 nm thick Li3N buffer layer was deposited on one surface of the base film to finally obtain a solid electrolyte membrane.
[0188] SEM scan of solid electrolyte membrane as shown in Figure Figure 2 As shown. (Through) Figure 2 Analysis reveals that the solid electrolyte membrane possesses a hierarchical structure formed by natural micron-sized channels and mesopores. Diatomaceous earth, cellulose nanofibers, and PVA form a 3D interpenetrating network. ZnO nanoparticles and GQDs are uniformly dispersed on the surface of the 3D network and within the porous interior, forming a dual ion-electron pathway. The high porosity of the membrane can accommodate more residual electrolyte phase, enhancing interfacial wettability. The Li3N buffer layer completely covers the surface of the solid electrolyte, preventing micro-short circuits during cycling.
[0189] The Fourier transform infrared (FTIR) spectrum of the solid electrolyte membrane is shown below. Figure 3 As shown. Figure 3 In the middle, located at 3400cm -1 The characteristic peak at 2350 cm⁻¹ represents the stretching vibration of residual hydroxyl groups / OH groups in adsorbed water. -1 The peak at 1720 cm⁻¹ corresponds to the stretching vibration of COC in cellulose nanofibers, indicating that the solid electrolyte membrane has formed a gel network; the peak at 1720 cm⁻¹ represents this stretching vibration. -1 The peak position corresponds to the C=O stretching vibration in the carboxyl group of GQDs, indicating the presence of conductive material in the solid electrolyte membrane. The peak at 1400 cm⁻¹ corresponds to this vibration. -1 The peak represents the COO of the carboxyl group in the binder CMC. - Symmetrical expansion and contraction, 1100cm -1 The characteristic peak is a result of Si-O-Si antisymmetric stretching in the SiO2 framework, indicating the presence of porous silica-oxygenated inorganic framework material in the solid electrolyte membrane. (1040 cm⁻¹) -1 The peak position is a result of the Si-OC vibration at the SiO2-GQDs interface; TFSI - The antisymmetric stretching of SNS in anions forms a structure located at 800 cm⁻¹ -1 The characteristic peak at 460 cm⁻¹ indicates the presence of lithium salt in the solid electrolyte membrane. -1 The characteristic peak at 420 cm⁻¹ is a result of the bending vibration of Zn-O in ZnO nanoparticles, indicating the presence of metal oxides in the solid electrolyte membrane. -1The characteristic peaks at this location are a result of N-Li lattice vibrations in the Li3N buffer layer, indicating that a Li3N buffer layer has formed in this solid electrolyte membrane. Figure 3 As can be seen, in Example 1 of the present invention, a solid electrolyte membrane of the target product was prepared.
[0190] Example 2 The method according to Example 1 differs in that: In the activation of diatomaceous earth: 80g of diatomaceous earth, 100mL of dilute hydrochloric acid, 300W microwave power, 30min microwave time, washed with deionized water until neutral, dried at 60℃ for 8h, transferred to a tube furnace and heated to 600℃ at 5℃ / min and held for 2h. The activated diatomaceous earth has a pore size PDI=0.71 and a surface roughness Ra=120nm. In the conductive material composite: 8g of graphene quantum dots (GQDs), 50mL of ethanol, 80g of activated diatomaceous earth, ultrasonic treatment for 20min (power 100W, frequency 30KHz), and mechanical stirring for 8h. In the raw material mixing process: 5g of LiTFSI, 200mL of cellulose nanofiber aqueous solution, and 1g of PVA crosslinking agent were used. The mixture was stirred at room temperature for 18 hours using a planetary mixer. During spray drying: inlet air temperature 100℃, feed rate 50mL / min, dehumidification in a 100℃ vacuum drying oven for 3 hours; In the dispersion of metal oxide nanoparticles: the final amount of dried particles collected by spray drying is 60g, the amount of ZnO nanoparticles is 8g, the amount of CMC binder is 1g, and the process is carried out by planetary ball milling (400rpm) for 1h. In cold pressing: the tablets are dried in a vacuum drying oven (80℃) for 1 hour.
[0191] The process was the same as in Example 1, and a base film (0.602 mm thick) and a corresponding solid electrolyte film were finally prepared.
[0192] Example 3 The method according to Example 1 differs in that: In the activation of diatomaceous earth: 100g of diatomaceous earth, 300mL of dilute hydrochloric acid, 500W microwave power, 60min microwave time, washed with deionized water until neutral, dried at 100℃ for 16h, transferred to a tube furnace and heated to 800℃ at 5℃ / min and held for 2h. The activated diatomaceous earth has a pore size PDI of 0.7 and a surface roughness of 125nm. In the conductive material composite: 12.5g of graphene quantum dots (GQDs), 80mL of ethanol, 100g of activated diatomaceous earth, ultrasonic treatment for 40min (power 300W, frequency 50KHz), and mechanical stirring for 16h. In the raw material mixing process: 15g of LiTFSI, 500mL of cellulose nanofiber aqueous solution, and 3g of PVA crosslinking agent were used. The mixture was stirred at room temperature for 30 hours using a planetary mixer. During spray drying: inlet air temperature 80℃, feed rate 20mL / min, dehumidification in a 60℃ vacuum drying oven for 1 hour; In the dispersion of metal oxide nanoparticles: the final amount of dried particles collected by spray drying is 100g, the amount of ZnO nanoparticles is 8g, the amount of CMC binder is 3g, and the process is carried out by planetary ball milling (400rpm) for 3h. In cold pressing: the tablets are dried in a vacuum drying oven (160℃) for 3 hours.
[0193] The process was the same as in Example 1, and a base film (0.793 mm thick) and a corresponding solid electrolyte film were finally prepared.
[0194] Example 4 The method according to Example 1 differs in that: Without the activation of diatomaceous earth in step S1, the diatomaceous earth in Example 1 is directly used for subsequent conductive material composite, intermediate preparation, mechanical mixing and cold pressing, and Li3N sputtering deposition.
[0195] The process was the same as in Example 1, and a base film (0.650 mm thick) and a corresponding solid electrolyte film were finally prepared.
[0196] Example 5 The method according to Example 1 differs in that: Without the conductive material composite in step S1, the activated diatomaceous earth from Example 1 is directly used for the preparation of subsequent intermediates, mechanical mixing and cold pressing, and Li3N sputtering deposition.
[0197] The process was the same as in Example 1, and a base film (0.803 mm thick) and a corresponding solid electrolyte film were finally prepared.
[0198] Example 6 The method according to Example 1 differs in that: Replace 2g of PVA crosslinking agent with 0.15g of gelatin.
[0199] The process was the same as in Example 1, and a base film (0.624 mm thick) and a corresponding solid electrolyte film were finally prepared.
[0200] Example 7 The method according to Example 1 differs in that: Replace ZnO nanoparticles with TiO2 nanoparticles (30 nm in diameter).
[0201] The process was the same as in Example 1, and a base film (0.798 mm thick) and a corresponding solid electrolyte film were finally prepared.
[0202] Example 8 The method according to Example 1 differs in that: Replace the CMC adhesive with the PAA adhesive.
[0203] The process was the same as in Example 1, and a base film (0.837 mm thick) and a corresponding solid electrolyte film were finally prepared.
[0204] Example 9 The method according to Example 1 differs in that: Replace LiTFSI with LiPF6.
[0205] The process was the same as in Example 1, and a base film (0.769 mm thick) and a corresponding solid electrolyte film were finally prepared.
[0206] Example 10 The method according to Example 1 differs in that: Replace the aqueous solution of cellulose nanofibers with an aqueous solution of carboxymethyl chitosan.
[0207] The process was the same as in Example 1, and a base film (0.695 mm thick) and a corresponding solid electrolyte film were finally prepared.
[0208] Example 11 The method according to Example 1 differs in that: In step S2, the mixing of raw materials is changed from stirring at room temperature for 24 hours to stirring at 60°C for 12 hours.
[0209] The process was the same as in Example 1, and a base film (0.702 mm thick) and a corresponding solid electrolyte film were finally prepared.
[0210] Example 12 The method according to Example 1 differs in that: Activated montmorillonite was prepared by replacing diatomaceous earth with montmorillonite (SiO2 mass content >95%, average particle size 2μm, pore size PDI=0.82, surface roughness=72nm). The activated montmorillonite had a pore size PDI=0.76 and a surface roughness Ra=138nm. The activated montmorillonite was then used for subsequent conductive material composites, intermediate preparation, mechanical mixing and cold pressing, and Li3N sputtering deposition.
[0211] The process was the same as in Example 1, and a base film (0.715 mm thick) and a corresponding solid electrolyte film were finally prepared.
[0212] Example 13 The method according to Example 1 differs in that: Graphene quantum dots (GQDs) were replaced with multi-walled carbon nanotubes (MWCNTs) with an average particle size of 20 nm.
[0213] The process was the same as in Example 1, and a base film (0.785 mm thick) and a corresponding solid electrolyte film were finally prepared.
[0214] Example 14 The method according to Example 1 differs in that: Instead of the non-conductive material composite step, graphene quantum dots (GQDs) (10g) and ZnO nanoparticles (5g, particle size 35nm) are dispersed together in ethanol in a metal oxide nanoparticle dispersion. Activated diatomaceous earth is also dispersed in ethanol for subsequent steps.
[0215] The process was the same as in Example 1, and a base film (0.807 mm thick) and a corresponding solid electrolyte film were finally prepared.
[0216] Comparative Example 1 The method according to Example 1 differs in that: Replace spray drying with vacuum heat preservation drying (vacuum degree <0.1Pa, temperature 110℃, time 12h).
[0217] The process was the same as in Example 1, and a base film (0.978 mm thick) and a corresponding solid electrolyte film were finally prepared.
[0218] Comparative Example 2 The method according to Example 1 differs in that: Without the Li3N sputtering deposition step, the base film in Example 1 is used as a solid electrolyte film.
[0219] Comparative Example 3 The method according to Example 1 differs in that: Instead of adding PVA crosslinking agent, replace the PVA crosslinking agent with a cellulose nanofiber solution (the mass of the cellulose nanofibers used in the replacement is the same as the mass of the PVA crosslinking agent).
[0220] The process was the same as in Example 1, and a base film (0.997 mm thick) and a corresponding solid electrolyte film were finally prepared.
[0221] Performance testing: (1) Ionic conductivity test: The solid electrolyte membrane was punched into a circular piece with a diameter of 10 mm, and the thickness was accurately measured to a tolerance range of ±1 μm. It was then equilibrated for 24 hours in a dry environment with a relative humidity of less than 5%. During the test, the sample was clamped between two mirror-polished stainless steel electrodes, and a constant pressure of 0.5 MPa was applied to ensure tight contact at the interface. The entire device was placed in a constant temperature chamber at 25 °C. A sinusoidal AC perturbation signal with a frequency range of 0.1 Hz to 1 MHz and an amplitude of 10 mV was applied through an electrochemical workstation, and Nyquist impedance spectrum data were collected. The bulk impedance value Rb was obtained by fitting the intersection of the high-frequency region and the real axis. Finally, the ionic conductivity was calculated by the formula σ = L / (Rb × A), where L is the membrane thickness and A is the effective contact area of the electrode.
[0222] (2) Mechanical property testing: According to GB / T 1040.3 standard, the solid electrolyte membrane was cut into dumbbell-shaped specimens with a gauge length of 20mm × 4mm. Each group of experiments contained at least 5 parallel samples. The specimens were pretreated in a constant temperature and humidity chamber at 23℃ and 50% relative humidity for 48 hours to eliminate environmental interference. Tensile tests were performed using a universal testing machine with an initial clamping distance of 50mm. The specimen was loaded at a constant rate of 10mm / min until it broke, and the stress-strain curve was recorded simultaneously. The tensile strength was determined by dividing the maximum load by the original cross-sectional area, and the elongation at break was calculated by the formula (gauge length at break - original gauge length) / original gauge length × 100%.
[0223] (3) Interfacial impedance characterization: In an argon glove box with oxygen and water content both below 0.1 ppm, a 200 μm thick lithium metal foil and a solid electrolyte membrane were assembled into a Li|electrolyte|Li symmetric battery structure, and then sealed under a pressure of 0.5 MPa. The battery was left to stand at 25 °C for 12 hours to achieve full interfacial contact activation. An electrochemical impedance spectroscopy was used to apply a 5 mV AC perturbation signal in the frequency range of 100 kHz to 0.1 Hz. The impedance value corresponding to the semicircle diameter in the high-frequency region of the Nyquist spectrum was the interfacial impedance (Rint). The stability of the system was determined by whether the interfacial impedance growth rate (ΔRint) after 100 cycles was below the threshold of 10%.
[0224] (4) Thermal stability analysis: 5.0 ± 0.2 mg of solid electrolyte membrane sample was pre-dried at 40 °C for 30 minutes to remove physically adsorbed water, and then placed in a thermogravimetric analyzer. Under the protection of a high-purity nitrogen flow rate of 50 mL / min, the temperature was programmed to rise from 25 °C to 800 °C at a heating rate of 10 °C / min. Key parameters included: the initial decomposition temperature (Td,5%) corresponding to a 5% weight loss, the peak temperature (Td,max) of the differential thermogravimetric curve (DTG), and the char residue rate (characterizing the inorganic filler content) during the 800 °C isothermal stage. Before testing, the temperature system needed to be calibrated using α-alumina standard material, with the accuracy controlled within ±1 °C.
[0225] (5) Characterization of porous structure: Solid electrolyte membrane samples were subjected to 120℃ and 10℃. -3 The adsorbate was completely removed by degassing under a high vacuum environment for 12 hours, and then transferred to a low-temperature nitrogen adsorption instrument. Nitrogen adsorption-desorption isotherms were tested at 77 K liquid nitrogen temperature, with relative pressure (P / P0) ranging from 0.01 to 0.99. Specific surface area was calculated by fitting a BET model in the P / P0 = 0.05–0.30 range; pore size distribution was analyzed using the BJH model based on desorption branch data; and porosity was calculated using the gas adsorption method.
[0226] The performance test results are shown in Table 1.
[0227] Table 1 Performance Test Results The results of the above performance tests show that, compared with the comparative example, the solid electrolyte membrane in this invention has better ionic conductivity, interfacial impedance, thermal stability and mechanical properties.
[0228] Compared to Example 1, Comparative Example 1, replacing spray drying with vacuum drying, resulted in a 99.5% decrease in ionic conductivity, a 72.3% decrease in tensile strength, a 72% decrease in elongation at break, a 1046% increase in interfacial impedance, a 68.2% decrease in thermal decomposition temperature, and a 51.7% decrease in porosity. This is attributed to vacuum drying causing capillary force aggregation, leading to material stacking and the disappearance of the porous structure. Comparative Example 2, lacking a Li3N buffer layer, showed a 95.8% decrease in ionic conductivity, a 959% increase in interfacial impedance, and a 50.6% decrease in thermal decomposition temperature compared to Example 1. This is attributed to the presence or absence of a Li3N buffer layer, which affects the sps of the conductive material GQDs. 2 -C domains directly contact lithium metal, undergoing a reduction reaction to form lithium dendrites that pierce the electrolyte membrane. In Comparative Example 3, without a crosslinking agent, the final ionic conductivity decreased significantly, tensile strength dropped sharply, elongation at break decreased sharply, interfacial impedance increased significantly, thermal decomposition temperature decreased significantly, specific surface area decreased, and porosity decreased. The reason for this is that the crosslinking agent can provide a chemical crosslinking network and enhance the structural stability of the cellulose skeleton. After removal, the membrane porosity decreased sharply (structural collapse), which led to the obstruction of ion transport channels (deterioration of ionic conductivity and interfacial impedance), and at the same time, the mechanical properties collapsed (the decrease in tensile strength and elongation at break corresponds to the loss of flexibility).
[0229] The parts of this invention not described in detail are techniques known to those skilled in the art.
[0230] The basic principles of the present invention have been described above with reference to specific embodiments. However, it should be noted that the advantages, benefits, and effects mentioned in the present invention are merely examples and not limitations, and should not be considered as essential features of each embodiment of the present invention. Furthermore, the specific details disclosed above are for illustrative and facilitative purposes only, and are not limitations. These details do not limit the present invention to the necessity of employing the aforementioned specific details.
[0231] In the foregoing description of this specification, references to terms such as "one embodiment," "another embodiment," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment is included in at least one embodiment of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples, without contradiction. Additionally, it should be noted that in this specification, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of indicated technical features.
[0232] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A solid electrolyte membrane, characterized in that, It includes a base film and a buffer layer disposed on at least one surface of the base film along its thickness direction; the porosity of the solid electrolyte membrane is not less than 20%. The base membrane comprises an inorganic framework, a gel electrolyte, and a binder; The inorganic framework comprises porous silica-oxygenated inorganic framework materials and metal oxides; The gel electrolyte comprises a flexible cross-linked polymer and a lithium salt.
2. The solid electrolyte membrane according to claim 1, characterized in that, The base membrane has a three-dimensional interpenetrating network structure; And / or, the buffer layer comprises at least one of Li3N, LLZO and Al2O3; And / or, the binder is distributed between the inorganic framework and the gel electrolyte; And / or, the adhesive includes at least one of CMC adhesive, PAA adhesive, PVA adhesive and PEO adhesive; And / or, the porous silica-oxygenated inorganic framework material and the metal oxide are bonded together by intermolecular forces to form an inorganic framework network; And / or, the porous silica-oxygenated inorganic framework material includes at least one of diatomaceous earth, zeolite, mesoporous silica and montmorillonite; And / or, the metal oxide includes at least one of ZnO, TiO2 and Al2O3; And / or, the flexible crosslinked polymer has a gel network structure composed of a natural polymer backbone and a crosslinked phase; And / or, the lithium salt is adsorbed onto the flexible cross-linked polymer to form an ion transport network; And / or, the lithium salt includes LiTFSI and / or LiPF6.
3. The solid electrolyte membrane according to claim 2, characterized in that, The mass ratio of the natural polymer backbone to the crosslinked phase is (0.5~7.5):1; And / or, the natural polymeric framework is formed from natural polymeric materials, including at least one of cellulose nanofibers, chitosan, and sodium alginate; And / or, the crosslinked phase is formed of a polymeric material having hydroxyl and / or carboxyl groups, the polymeric material having hydroxyl and / or carboxyl groups including at least one of polyvinyl alcohol, gelatin, carboxymethyl chitosan and natural rubber.
4. The solid electrolyte membrane according to claim 1, characterized in that, The base film further includes a conductive material, which satisfies at least one of the following characteristics (1) to (4): (1) The conductive material is loaded on the porous silica-oxygenated inorganic framework material to form a charge transport network; (2) The conductive material has C=O groups, and the C=O groups in the conductive material are bonded to the Si-O-Si in the porous silica-oxygen inorganic framework material by hydrogen bonds; (3) The conductive material includes carbon-based conductive materials; the carbon-based conductive material includes at least one of graphene quantum dots, multi-walled carbon nanotubes and graphene oxide; (4) The mass ratio of the conductive material to the porous silica-oxygenated inorganic framework material is 1: (8~10).
5. The solid electrolyte membrane according to any one of claims 1 to 4, characterized in that, The porosity of the solid electrolyte membrane is 22%~40%; And / or, the specific surface area of the solid electrolyte membrane is 100 m². 2 / g~220m 2 / g; And / or, the inorganic framework has a mass content of 29% to 85% in the base film; And / or, the gel electrolyte has a mass content of 5% to 67% in the base membrane; And / or, the adhesive content in the base film is 1% to 15% by mass; And / or, the mass ratio of the porous silica-oxygenated inorganic framework material to the metal oxide is (1.25~15):1; And / or, the mass ratio of the lithium salt to the flexible crosslinked polymer is (0.5~6):1; And / or, the thickness of the base film is 0.5 mm to 1 mm; And / or, the thickness of the buffer layer is 20nm~40nm.
6. A method for preparing a solid electrolyte membrane according to any one of claims 1 to 5, characterized in that, Includes the following steps a) A slurry containing a porous silica-oxygenated inorganic framework material is first mixed with a solution containing a gel precursor, a lithium salt, and a crosslinking agent to obtain a mixed slurry; then the mixed slurry is spray-dried to obtain an intermediate. b) The intermediate obtained in step a) and the metal oxide are ball-milled to obtain a ball milling material; then, in the presence of water, the binder is mixed with the ball milling material for the second time, and then the mixture is successively molded and dried to obtain a base film; c) Deposit a buffer material onto the base film obtained in step b) to form a buffer layer, thereby obtaining a solid electrolyte membrane.
7. The preparation method according to claim 6, characterized in that, In step a), the conditions for the first mixing include: stirring at room temperature for 18 to 30 hours; And / or, in step a), the conditions for spray drying include: an inlet air temperature of 80℃~100℃, an outlet temperature of 60℃~70℃, an atomization pressure of 0.2MPa~0.3MPa, and a feed rate of 30mL / min~40mL / min; And / or, in step b), the ball milling is wet ball milling, and the conditions for wet ball milling include: a rotation speed of 200 rpm to 500 rpm and a time of 1 h to 3 h; And / or, in step b), the conditions for the second mixing include: stirring at room temperature for 0.5 h to 2 h; And / or, in step b), the molding is cold pressing, and the conditions for cold pressing include: temperature of 20℃~30℃, pressure of 10MPa~20MPa, and time of 1min~10min; And / or, in step c), the deposition is performed by chemical vapor deposition, wherein the conditions of the chemical vapor deposition include: a substrate temperature of 100°C to 300°C and a sputtering power of 0.1 kW / cm². 2 ~1kW / cm 2 The working gas is an inert gas, the deposition working gas pressure is 0.2 Pa to 1.5 Pa, and the deposition time is 10 min to 30 min.
8. The preparation method according to claim 6, characterized in that, The porosity of the porous silica-oxygenated inorganic framework material is >90%; And / or, the pore size PDI of the porous silica-oxygenated inorganic framework material is 0.6~0.75; And / or, the surface roughness Ra of the porous silica-oxygenated inorganic framework material is 50 nm to 200 nm; And / or, the porous silica-oxygenated inorganic framework material includes at least one of diatomaceous earth, zeolite, mesoporous silica and montmorillonite; And / or, the porous silica-oxygenated inorganic framework material includes porous silica-oxygenated inorganic framework material that has undergone acid treatment, washing, drying, and calcination; The acid treatment conditions include: microwave pickling in the presence of dilute hydrochloric acid; the calcination conditions include: calcination under an inert atmosphere at a temperature of 600℃~800℃ for 1h~3h. And / or, the gel precursor comprises a natural polymer material, which includes at least one of cellulose nanofibers, chitosan, and sodium alginate; And / or, the crosslinking agent comprises a polymeric material having hydroxyl and / or carboxyl groups; And / or, the average molecular weight of the crosslinking agent is 85000 g / mol to 130000 g / mol; And / or, the intermediate Dv 50 Particle size ranges from 5 μm to 10 μm; And / or, the particle size of the metal oxide is 10 nm to 50 nm; And / or, the buffer material includes at least one of Li3N, LLZO and Al2O3; And / or, the slurry comprising the porous silica-oxygenated inorganic framework material further comprises a conductive material, and / or a conductive material is added during the ball milling process; the mass ratio of the conductive material to the porous silica-oxygenated inorganic framework material is 1:(8~10).
9. The preparation method according to any one of claims 6 to 8, characterized in that, The solid content of the mixed slurry is 10%~30%; And / or, the mass ratio of the porous silica-oxygenated inorganic framework material to the gel precursor is (5~45):(1.5~7.5); And / or, the mass ratio of the gel precursor to the lithium salt is (0.5~7.5):(5~15); And / or, the mass ratio of the gel precursor to the crosslinking agent is (1.5~7.5):(1~3); And / or, the mass ratio of the porous silica-oxygenated inorganic framework material to the metal oxide is (2~20):(1~8); And / or, the mass ratio of the porous silica-oxygenated inorganic framework material to the binder is (10~60):(1~3).
10. A battery, characterized in that, It includes a positive electrode, a negative electrode, and a solid electrolyte membrane disposed between the positive electrode and the negative electrode; the solid electrolyte membrane includes the solid electrolyte membrane according to any one of claims 1 to 5 or the solid electrolyte membrane prepared by the preparation method of the solid electrolyte membrane according to any one of claims 6 to 9.